Clinical use and applications of a citrate-based antiseptic lavage for the prevention and treatment of PJI - Valdés, Daniel Alejandro; Minter, Jon E. (Frontiers in Medicine, 2024)
Total joint arthroplasties (TJA) are some of the most commonly performed surgeries in the United States with the number of TJA expected to rise significantly over the next decade as the population ages and arthritic burden worsens. However, the rise in TJA volume correlates with a heightened risk of complications, notably prosthetic joint infections (PJI), despite their low occurrence rate of less than 2%. PJI imposes a significant burden on surgery success, patient well-being, and healthcare costs, with an estimated annual expense of 1.85 billion dollars for hip and knee PJI by 2030. This manuscript delves into the pathophysiology of PJI, exploring our current understanding of the role of bacterial biofilm formation on implanted foreign hardware, providing protection against the host immune system and antibiotics. The article reviews current agents and their efficacy in treating PJI, as well as their cytotoxicity towards native cells involved in wound healing, prompting the exploration of a novel citrate-based solution. The paper highlights the superior properties and efficacy of a novel citrate-based irrigation solution on the treatment and prevention of PJI via increased antimicrobial properties, greater biofilm disruption, increased exposure time, and reduced cytotoxicity compared to conventional solutions, positioning it as a promising alternative. It also provides a perspective on its clinical use in the operating theatre, with a step-by-step approach in TJA, whether primary or revisionary.